Export Barriers and Stimuli in the Russian Federation - Mikalai Dudko (Entrepreneurial Business and Economics Review)
The purpose of this article is to identify and analyse existing export barriers and stimuli in the Russian Federation. The gravity model is used to identify and assess impact of informal export barriers and stimuli. Qualitative approach and statistical analysis is used to identify and assess the impact of formal barriers and stimuli.